Cadmium metal organic framework material, composite membrane material and preparation method and application thereof
By using cadmium metal organic frame material (Cd-MOF) and its composite film material (Cd-MOF@EC) as friction electrode materials, TENG devices are constructed, and the problems of unstable output performance and short service life of existing TENG electrode materials are solved, and the C-H bond azide reaction and self-powered driving of visible light-induced aldehyde-based compounds are achieved.
Patent Information
- Application Number
- CN202310474864.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-27
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2043-04-27
AI Technical Summary
Existing friction nanogenerators (TENGs) have problems with unstable output performance and short service life in terms of electrode materials, and it is difficult to effectively utilize visible light to induce C-H bond azide reaction of aldehyde-based compounds.
Cd-MOF is used as friction electrode materials, and Cd-MOF is synthesized by hydrothermal method and is composited with ethyl cellulose (EC) to form Cd-MOF@EC composite membrane material, which is used to construct TENG devices.
The good output performance and excellent cyclic stability of the Cd-MOF@EC-TENG device were achieved, and the cyclic stability of 14 1-watt white lamp bead groups were continuously driven, and the azide reaction of the C-H bond of the aldehyde-based compound was successfully achieved.
Smart Images

Figure CN116589692B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of inorganic materials, and specifically relates to the preparation of cadmium metal organic framework materials (Cd-MOF) and the construction of a friction nanogenerator (TENG) using composite film materials thereof to realize visible light-induced azidation reaction of CH bonds of aldehyde compounds. Technical Background
[0002] With the vigorous development of global industry, energy shortage and environmental pollution have become urgent problems for all countries. In order to alleviate the energy crisis and improve environmental problems, the development of sustainable green energy has become a necessary means and goal. However, there is a large amount of useless mechanical energy in the natural and social environment, such as raindrop energy, tidal energy, and human body movement. If these useless mechanical energies can be fully utilized and converted into energy needed by humans through reasonable means, this will provide a feasible solution to the energy and environmental problems we face. As an energy conversion device, the friction nanogenerator (TENG) can effectively collect low-frequency signals in the surrounding environment and convert useless mechanical energy into useful electrical energy. At the same time, TENG has the characteristics of high output frequency, simple structure, diverse output methods, no waste generation, and green environmental protection. It provides a feasible solution to the problem of power sustainability in today's lightweight and miniaturized electronic equipment.
[0003] Metal-organic framework materials (MOFs) are coordination compounds formed by metal ions and bridging ligands through coordination bonds. They have the characteristics of large specific surface area and unique pore structure. Therefore, they have broad application prospects in gas adsorption separation, chiral separation and drug controlled release. And it is precisely because of the structural characteristics of MOFs themselves and the convenient synthesis and operability that their synthetic structure can be flexible and changeable, and predictable synthetic strategies can be achieved through appropriate means. The friction mechanism of TENG is the coupling effect of triboelectric charging and electrostatic induction. Therefore, suitable electrode materials are the key issues to improve the output performance of TENG and realize its practical application. Cd ions, as transition metals, have unstable extranuclear electrons. When different electrode materials come into contact, they can more conveniently excite extranuclear electrons. Therefore, Cd-MOFs are potential excellent materials for improving the output performance of TENG, and are also conducive to expanding the triboelectric sequence materials of MOFs. In addition, MOFs are difficult to grow in situ, so we thought of using the mold casting method to form a film to form the obtained MOFs material. The obtained membrane material not only further improves the output performance of triboelectricity, but also increases the service life of the electrode material, making the output more stable. Finally, we used the obtained Cd-MOF material and Cd-MOF@EC composite membrane material to form a counter electrode with PVDF, and the constructed TENG can continuously power the white lamp bead group, realizing the visible light-induced CH bond azidation reaction of aldehyde compounds. Summary of the invention
[0004] The present invention discloses a preparation method and application of a cadmium metal-organic framework Cd-MOF material and its composite film. The prepared Cd-MOF and its Cd-MOF@EC (ethyl cellulose) composite film material are used as friction electrode materials to construct a TENG device with good output performance and excellent cycle stability. The device is applied to a self-driven lighting white small lamp bead group, realizing the visible light-induced azidation reaction of the CH bond of the aldehyde compound.
[0005] In order to solve the above technical problems, the present invention adopts the following technical solutions:
[0006] A cadmium metal organic framework material Cd-MOF, the molecular structure of which is [Cd2(CBBD)(4,4ʹ-bpy)(EtOH)2] n , n=∞, the Cd-MOF unit structure is as follows:
[0007] .
[0008] The preparation method of the cadmium metal-organic framework material Cd-MOF comprises the following steps:
[0009] (1) H4CBBD (4',4'''-carbonylbis(([1,1'-biphenyl]-3,5-dicarboxylicacid))), terminal bridging ligand 4,4'-bipyridine (4,4'-bpy) and Cd(NO3)2·4H2O were placed into a polytetrafluoroethylene liner, and then a mixed solvent consisting of water and ethanol was added, and the mixture was stirred and mixed to obtain a mixed solution;
[0010] (2) The encapsulated polytetrafluoroethylene liner loaded in step (1) is loaded into a reactor and placed in an oven for hydrothermal reaction. After the reaction time is over, the temperature is lowered to the desired temperature and then the oven is closed. After naturally cooling to room temperature, the oven is taken out and the crystal growth condition is observed under a microscope. The mixture is then filtered, allowed to stand, and allowed to dry naturally to obtain a cadmium metal organic framework material Cd-MOF.
[0011] Furthermore, in step (1), the molar ratio of the ligand H4CBBD, the terminal bridging ligand 4,4'-bpy and Cd(NO3)2·4H2O is 1:2:2; based on 0.1 mmol Cd(NO3)2·4H2O, 4-7 mL of water and ethanol are required.
[0012] Furthermore, in the step (2), the temperature of the hydrothermal reaction is 160°C, and the time of the hydrothermal reaction is 48-72 h. After the reaction is completed, the temperature is lowered to 80°C at a rate of 5°C / h, and then the temperature is stopped and the oven is closed. The oven is allowed to cool naturally to room temperature, and colorless crystals are obtained, namely, Cd-MOF crystal materials.
[0013] The application of the cadmium metal-organic framework material Cd-MOF prepared by the preparation method of the present invention as a friction electrode material in constructing Cd-MOF-TENG comprises the following steps:
[0014] a. Weigh the dried cadmium metal Cd-MOF crystal material and grind it into micrometer-level crystal powder material by mechanical grinding, and the size of the crystal powder material is 1-100 μm;
[0015] b. Apply the crystal powder material evenly on the sticky surface of the Cu tape, remove the excess powder with an air gun, stick the copper wire on the back of the copper sheet as the external conductor, and cut it into 5 × 5 cm 2 ;
[0016] c. Spin-coat polyvinylidene fluoride (PVDF) into a film, stick it on a copper sheet, and cut it into 5 × 6 cm 2 , and paste copper wire on the back of the copper sheet as another external conductor;
[0017] d. Assemble the devices prepared in b and c above into a powder Cd-MOF-TENG device;
[0018] The method for preparing a Cd-MOF@EC composite film material by using the cadmium metal-organic framework material Cd-MOF of the present invention as a friction electrode material comprises the following steps:
[0019] (1) Grinding the Cd-MOF crystal material into a micrometer-level material by mechanical grinding to obtain a crystal powder material with a size of 1-100 μm, and then ultrasonically dispersing the crystal powder material in a DMF solution;
[0020] (2) Weigh 400 mg of EC powder, add 6 ml of DMF, then heat at 100 °C and stir for 30-60 min until completely dissolved, then transfer to room temperature; add the reaction system solution in step (1) to the dissolved EC and stir at room temperature for 4-8 h;
[0021] (3) The mixed solution of (2) was poured into a glass mold and cured at 80°C-120°C for 0.5 h. After cooling, the mold was removed to obtain a Cd-MOF@EC composite membrane material.
[0022] Furthermore, the mass ratio of the Cd-MOF crystal material to the EC powder is ((0.03-0.2):1.
[0023] The present invention also provides a Cd-MOF@EC composite membrane material prepared by the method.
[0024] The present invention applies Cd-MOF@EC composite film material to a triboelectric nanogenerator (TENG) to promote visible light-induced CH bond azidation reaction of aldehyde compounds, comprising the following steps:
[0025] a. Cut the film into 5×5 cm 2 , glued to the sticky side of the Cu tape and bonded copper wire on the back with conductive silver glue as an external conductor;
[0026] b. Spin-coat the PVDF film onto the copper sheet and cut it into 5 × 6 cm 2 , and paste copper wire on the back of the copper sheet as another external conductor;
[0027] c. Assembling the devices prepared in a and b above into a Cd-MOF@EC-TENG device based on Cd-MOF@EC composite film material;
[0028] d. Connect the Cd-MOF@EC-TENG device and continuously power the white lamp bead group to provide a white light source to achieve visible light-induced azidation reaction of the CH bonds of aldehyde compounds.
[0029] The present invention tested the current, voltage and load values of Cd-MOF composite film materials with different contents. The experimental results showed good output performance and excellent stability. The self-powered Cd-MOF@EC-TENG device was successfully used to drive a white lamp bead group for visible light-induced CH bond azidation reaction of aldehyde compounds.
[0030] Beneficial effects of the present invention: 1. The TENG device constructed with Cd-MOF and its Cd-MOF@EC composite film materials is applied to the visible light-induced CH bond azidation reaction of aldehyde compounds, constructing a new type of friction material with good output performance and excellent cycle stability, and preparing it into a TENG device, which is applied to the CH bond azidation reaction of aldehyde compounds, realizing self-powered photochemical reaction.
[0031] 2. The maximum short-circuit current ( I sc ), charge density (σ), and maximum power density reached 81.34μA and 113μC / m 2 , 3352.46 mW / m -2 , can continuously drive 14 1-watt white lamp beads to provide visible light source.
[0032] 3. The Cd-MOF crystal material in the present invention has good stability, remains stable below 320°C, and can maintain a good morphology during the entire collision process, laying the foundation for continuous use. It can also maintain long-term cycle stability of up to 50,000 working cycles at an impact frequency of 5 Hz; and completes the visible light-induced CH bond azidation reaction of aldehyde compounds within 8-10 hours. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 This is the structural diagram of the H4CBBD ligand used in material preparation.
[0034] Figure 2 This is the crystal structure diagram of Cd-MOF material.
[0035] Figure 3 This is the thermogravimetric analysis diagram of Cd-MOF material.
[0036] Figure 4 is a picture of Cu tape made of Cd-MOF@EC composite film.
[0037] Figure 5 This is the current diagram of the powder Cd-MOF-TENG device at an impact frequency of 5 Hz.
[0038] Figure 6 This is the voltage diagram of the powder Cd-MOF-TENG device at 5Hz impact frequency
[0039] Figure 7 is the current diagram of the powder Cd-MOF-TENG device under different impact frequencies.
[0040] Figure 8 is the voltage diagram of the powder Cd-MOF-TENG device under different impact frequencies.
[0041] Fig. 9 It is the power diagram of the powder Cd-MOF-TENG device at an impact frequency of 5 Hz.
[0042] Fig.10 This is the current diagram of the Cd-MOF@EC-TENG device at an impact frequency of 5 Hz.
[0043] Fig.11 This is the voltage diagram of the Cd-MOF@EC-TENG device at an impact frequency of 5 Hz.
[0044] Fig.12 is the current diagram of the Cd-MOF@EC-TENG device under different impact frequencies.
[0045] Fig.13It is the voltage diagram of Cd-MOF@EC-TENG device under different impact frequencies.
[0046] Fig.14 It is the power diagram of Cd-MOF@EC-TENG device under 5 Hz impact frequency.
[0047] Fig.15 This is the cyclic stable current diagram of the powder Cd-MOF-TENG device after an impact frequency of 5 Hz.
[0048] Fig.16 This is the cyclic stable current diagram of the Cd-MOF@EC composite film TENG device with 15% content after an impact frequency of 5 Hz.
[0049] Fig.17 This is a group picture of a white lamp bead lit up by a 15% Cd-MOF@EC composite film TENG device at an impact frequency of 5Hz. DETAILED DESCRIPTION
[0050] The above contents of the present invention are further described in detail below through examples, but this should not be understood as the scope of the above subject matter of the present invention being limited to the following examples, and all technologies implemented based on the above contents of the present invention belong to the scope of the present invention.
[0051] Example 1: Preparation of crystalline Cd-MOF material
[0052] (1) Cd(NO3)2·4H2O (0.0308 g, 0.1 mmol), 4,4ʹ-bpy (0.0234 g, 0.1 mmol) and H4CBBD (0.0255 g, 0.05 mmol) were added to the inner lining of a 25 mL polytetrafluoroethylene reactor, and 4 ml of water and 4 ml of ethanol were added.
[0053] (2) After the reaction system is sealed, place it in an oven at 160°C and react for 72 hours. After the reaction is completed, the temperature is gradually reduced by 5°C per hour to 80°C and the oven is closed.
[0054] (3) Drying the crystals obtained in step (2) to obtain cadmium metal Cd-MOF crystal materials.
[0055] (4) Cd-MOF (1) The crystallographic parameters are shown in the following table:
[0056]
[0057] Example 2: Preparation of TENG devices constructed from powdered Cd-MOF
[0058] (1) Grinding the Cd-MOF crystal material into micrometer-level particles with a size of 1-100 μm by mechanical grinding;
[0059] (2) Apply the ground crystal powder material evenly on the sticky surface of the Cu tape, and remove excess powder with an air gun;
[0060] (3) Paste the copper wire on the back of the copper sheet as the external conductor and cut it into 5×5cm 2 ;
[0061] (4) Prepare a 5×6 cm PVDF film by spin coating 2 , and paste it on the copper sheet, and paste the copper wire on its back to form another external conductor;
[0062] (5) The above (3) and (4) were assembled into a Cd-MOF-TENG device. The test showed that the current value could reach 50 μA and the charge density was 94 μC / m 2 ( Figure 5 );
[0063] Example 3: Preparation of 3% Cd-MOF@EC composite film TENG device
[0064] (1) Take 12 mg of the Cd-MOF crystalline powder material ground into micrometer level in step (1) of Example 2, and ultrasonically disperse it in 2 mL of DMF;
[0065] (2) Weigh 400 mg of EC powder, add 6 mL of DMF, heat at 100 °C and stir for 30 min until completely dissolved, then transfer to room temperature;
[0066] (3) Add the dispersed crystalline powder to the dissolved EC and stir at room temperature for 4 h;
[0067] (4) Pour the dispersed mixed solution into a glass mold, cure at 80 °C for 0.5 h, and then cool and remove the mold to obtain a Cd-MOF@EC composite film;
[0068] (5) Cut the Cd-MOF@EC composite film into 5×5 cm 2 , and stick it on the sticky side of the Cu tape; at the same time, stick copper wire on the back of the copper tape as an external wire;
[0069] (6) Paste the spin-coated PVDF film onto the copper sheet and cut it into 5×5 cm 2 ; At the same time, a copper wire is pasted on the back side as another external conductor;
[0070] (7) The above (5) and (6) were assembled into Cd-MOF@EC TENG devices, and the current value was tested to reach 34 μA.
[0071] Example 4: Preparation of 5% Cd-MOF@EC composite film TENG device
[0072] (1) Take 21 mg of the Cd-MOF crystalline powder material ground into micrometer level in step (1) of Example 2, and ultrasonically disperse it in 2 mL of DMF;
[0073] (2) Weigh 400 mg of EC powder, add 6 mL of DMF, heat at 100 °C and stir for 30 min until completely dissolved, then transfer to room temperature;
[0074] (3) Add the dispersed crystalline powder to the dissolved EC and stir at room temperature for 4 h;
[0075] (4) Pour the dispersed mixed solution into a glass mold, cure at 120 °C for 1 h, and then cool and demold to obtain a Cd-MOF@EC composite film;
[0076] (5) Cut the Cd-MOF@EC composite film into 5×5 cm 2 , and stick it on the sticky side of the Cu tape; at the same time, stick copper wire on the back of the copper tape as an external wire;
[0077] (6) Paste the spin-coated PVDF film onto the copper sheet and cut it into 5×5 cm 2 ; At the same time, a copper wire is pasted on the back side as another external conductor;
[0078] (7) The above (5) and (6) were assembled into Cd-MOF@EC TENG devices, and the current value was tested to reach 43μA ( Fig.14 ).
[0079] Example 5: Preparation of 10% Cd-MOF@EC composite film TENG device
[0080] (1) Take 44.4 mg of the Cd-MOF crystalline powder material ground into micrometer level in step (1) of Example 2, and disperse it in 2 mL of DMF by ultrasonication;
[0081] (2) Weigh 400 mg of EC powder, add 6 mL of DMF, heat at 100 °C and stir for 30 min until completely dissolved, then transfer to room temperature;
[0082] (3) Add the dispersed crystalline powder to the dissolved EC and stir at room temperature for 4 h;
[0083] (4) Pour the dispersed mixed solution into a glass mold, cure at 80 °C for 0.5 h, and then cool and remove the mold to obtain a Cd-MOF@EC composite film;
[0084] (5) Cut the Cd-MOF@EC composite film into 5×5 cm2 , and stick it on the sticky side of the Cu tape; at the same time, stick copper wire on the back of the copper tape as an external wire;
[0085] (6) Paste the spin-coated PVDF film onto the copper sheet and cut it into 5×5 cm 2 ; At the same time, a copper wire is pasted on the back side as another external conductor;
[0086] (7) The above (5) and (6) were assembled into Cd-MOF@EC TENG devices, and the current value was tested to reach 60μA.
[0087] Example 6: Preparation of 15% Cd-MOF@EC composite film TENG device
[0088] (1) Take 70.6 mg of the Cd-MOF crystalline powder material ground into micrometer level in step (1) of Example 2, and ultrasonically disperse it in 2 mL of DMF;
[0089] (2) Weigh 400 mg of EC powder, add 6 mL of DMF, heat at 100 °C and stir for 30 min until completely dissolved, then transfer to room temperature;
[0090] (3) Add the dispersed crystalline powder to the dissolved EC and stir at room temperature for 4 h;
[0091] (4) Pour the dispersed mixed solution into a glass mold, cure at 80°C for 0.5 h, cool and then demold to obtain a Cd-MOF@EC composite film;
[0092] (5) Cut the Cd-MOF@EC composite film into 5×5 cm 2 , and stick it on the sticky side of the Cu tape; at the same time, stick copper wire on the back of the copper tape as an external wire;
[0093] (6) Paste the spin-coated PVDF film onto the copper sheet and cut it into 5×5 cm 2 ; At the same time, a copper wire is pasted on the back side as another external conductor;
[0094] (7) The above (5) and (6) were assembled into Cd-MOF@EC TENG devices, and the current value was tested to reach 80μA ( Fig.10 ).
[0095] Example 7: Preparation of 20% Cd-MOF@EC composite film TENG device
[0096] (1) Take 100 mg of the Cd-MOF crystalline powder material ground into micrometer level in step (1) of Example 2, and ultrasonically disperse it in 2 mL of DMF;
[0097] (2) Weigh 400 mg of EC powder, add 6 mL of DMF, heat at 100 °C and stir for 30 min until completely dissolved, then transfer to room temperature;
[0098] (3) Add the dispersed crystalline powder to the dissolved EC and stir at room temperature for 4 h;
[0099] (4) Pour the dispersed mixed solution into a glass mold, cure at 80 °C for 0.5 h, cool and then demold to obtain a Cd-MOF@EC composite film;
[0100] (5) Cut the Cd-MOF@EC composite film into 5×5 cm 2 , and stick it on the sticky side of the Cu tape; at the same time, stick copper wire on the back of the copper tape as an external wire;
[0101] (6) Paste the spin-coated PVDF film onto the copper sheet and cut it into 5×5 cm 2 ; At the same time, a copper wire is pasted on the back side as another external conductor;
[0102] (7) The above (5) and (6) were assembled into Cd-MOF@EC TENG devices, and the current value was tested to reach 62μA.
[0103] Example 8: Cyclic stability test of 15% Cd-MOF@EC composite film TENG device.
[0104] (1) The Cd-MOF@EC-TENG device in Example 6 was continuously tested at 1-8 Hz, and the current values were obtained from 1 Hz to 8 Hz. As the impact frequency increased, the current increased, which were 20.54 μA, 32.03 μA, 58.57 μA, 94.22 μA, and 149.49 μA, respectively ( Fig.12 ).
[0105] (2) The Cd-MOF@PEC-TENG device in Example 6 was continuously tested at 5 Hz, and the current value was 80 μA, with no obvious attenuation after 50,000 cycles ( Fig.16 ).
[0106] (3) The Cd-MOF@EC-TENG device in Example 6 was continuously tested at 5 Hz, and its maximum power density under different loads was 3352.46 mW / m -2 ( Fig.14 ).
[0107] Example 9. Photoinduced CH azidation reaction of benzaldehyde
[0108] (1) Add benzaldehyde (1 mmol), CBr4 (0.5 mmol), sodium azide (3 mmol) and CH3CN (3 mL) into an ampoule.
[0109] (2) The drugs prepared in step (1) are placed in an ampoule, mixed and placed in a vacuum.
[0110] (3) Using the Cd-MOF@EC-TENG device of Example 6, 14 1W visible light lamp beads were driven to illuminate the room temperature reaction ( Fig.17 ).
[0111] (4) After column chromatography (EA / PE = 1:10), 164.71 mg (91%) of a white solid was obtained. This compound has been reported. 1 H NMR (400 MHz, CDCl3), δ: 7.43 (d, J=8.0 Hz, 2H), 7.35 (d, J=8.0 Hz, 2H).
[0112] Example 10: Photoinduced CH azidation of p-Anisaldehyde
[0113] (1) Add p-anisaldehyde (1 mmol), CBr4 (0.5 mmol), sodium azide (3 mmol) and CH3CN (3 mL) into an ampoule.
[0114] (2) The drugs prepared in step (1) are placed in an ampoule, mixed and placed in a vacuum.
[0115] (3) Use the Cd-MOF@EC-TENG device of Example 6 to drive and light up a group of 14 1 W visible light lamp beads for irradiation and reaction at room temperature.
[0116] (4) After the reaction was completed, column chromatography (EA / PE=1:10) gave 139.69 mg (95%) of a colorless oil. This compound has been reported. 1 H NMR (400 MHz, CDCl3), δ: 7.84-7.87 (m, 2H), 7.57-7.61 (m, 1H), 7.47-7.51 (m, 2H).
[0117] Example 11: Photoinduced CH azidation of p-methylbenzaldehyde
[0118] (1) Add p-tolualdehyde (1 mmol), CBr4 (0.5 mmol), sodium azide (3 mmol) and CH3CN (3 mL) into an ampoule.
[0119] (2) The drugs prepared in step (1) are placed in an ampoule, mixed and placed under vacuum.
[0120] (3) Use the Cd-MOF@EC-TENG device of Example 6 to drive and light up a group of 14 1 W visible light lamp beads for irradiation and reaction at room temperature.
[0121] (4) After column chromatography (EA / PE=1:10), 164.65 mg (91%) of a colorless oil was obtained. This compound has been reported. 1 H NMR (400 MHz, CDCl3), δ: 7.71-7.74 (m, 2H), 7.50-7.56 (m, 1H), 7.34 (m), 1H, 2.41 (s, 3H).
[0122] Example 12: Photoinduced CH azidation of 3-methylbenzaldehyde
[0123] (1) Add 3-methylbenzaldehyde (1 mmol), CBr4 (0.5 mmol), sodium azide (3 mmol) and CH3CN (3 mL) into an ampoule.
[0124] (2) The drugs prepared in step (1) are placed in an ampoule, mixed and placed in a vacuum.
[0125] (3) Use the Cd-MOF@EC-TENG device of Example 6 to drive and light up a group of 14 1 W visible light lamp beads for irradiation and reaction at room temperature.
[0126] (4) After column chromatography (EA / PE=1:10), 168.20 mg (94%) of a colorless oil was obtained. This compound has been reported. 1 H NMR (400 MHz, CDCl3), δ: 7.46 (d, J=8.0 Hz, 2H), 7.28 (d, J=8.0 Hz (2H)), 2.39 (s, 3H).
[0127] Example 13: Photoinduced CH azidation of 2-methylbenzaldehyde
[0128] (1) Add 2-methylbenzaldehyde (1 mmol), CBr4 (0.5 mmol), sodium azide (3 mmol) and CH3CN (3 mL) into an ampoule.
[0129] (2) The drugs prepared in step (1) are placed in an ampoule, mixed and placed under vacuum.
[0130] (3) Use the Cd-MOF@EC-TENG device of Example 6 to drive and light up a group of 14 1 W visible light lamp beads for irradiation and reaction at room temperature.
[0131] (4) After column chromatography (EA / PE = 1:10), 168.20 mg (95%) of a light yellow solid was obtained. This compound has been reported.1 H NMR (400 MHz, CDCl3), δ: 7.98-8.09 (m, 2H), 7.50-7.54 (m, 2H), 3.85 (s, 3H).
[0132] Example 14: Photoinduced CH azidation of p-chlorobenzaldehyde
[0133] (1) Add p-chlorobenzaldehyde (1 mmol), CBr4 (0.5 mmol), sodium azide (3.3 mmol) and CH3CN (3 mL) into an ampoule.
[0134] (2) The drug prepared in step (1) is placed in an ampoule, mixed and irradiated with a visible light source in a vacuum.
[0135] (3) Use the Cd-MOF@EC-TENG device of Example 6 to drive and light up a group of 14 1 W visible light lamp beads for irradiation and reaction at room temperature.
[0136] (4) After column chromatography (EA / PE=1:10), 154.03 mg (87%) of a colorless oil was obtained. This compound has been reported. 1 H NMR (400 MHz, CDCl3), δ: 7.76-7.84 (m, 2H), 7.51-7.55 (m, 1H), 7.29 (s, 1H, 2.43 (s, 3H).
[0137] Example 15: Photoinduced CH azidation of 4-nitrobenzaldehyde
[0138] (1) Add 4-nitrobenzaldehyde (1 mmol), CBr4 (0.5 mmol), sodium azide (3.3 mmol) and CH3CN (3 mL) into an ampoule.
[0139] (2) The drugs prepared in step (1) are placed in an ampoule, mixed and placed in a vacuum.
[0140] (3) Use the Cd-MOF@EC-TENG device of Example 6 to drive and light up a group of 14 1 W visible light lamp beads for irradiation and reaction at room temperature.
[0141] (4) After column chromatography (EA / PE=1:10), 165.14 mg (86%) of a white solid was obtained. This compound has been reported. 1 HNMR (400 MHz, CDCl3), δ: 8.29 (m, 2H), 8.15 (m, 2H).
[0142] The Cd-MOF of the present invention can be controllably synthesized by solvothermal method, which expands the selection range of triboelectric series materials and effectively improves the output performance of triboelectric nanogenerators. Experimental results show that the Cd-MOF@EC-TENG device has excellent output stability and realizes the self-driven visible light-induced CH bond azidation reaction of aldehyde compounds. Therefore, the preparation of Cd-MOF and its composite film can become a potential output electrode material.
[0143] The above embodiments describe the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for illustrating the principles of the present invention. Without departing from the scope of the principles of the present invention, the present invention may have various changes and improvements, and these changes and improvements all fall within the scope of protection of the present invention.
Claims
1. A method for preparing a Cd-MOF@EC composite membrane material, characterized in that: The following steps are involved: 1) Grinding the cadmium metal organic framework material Cd-MOF into a micrometer-level crystalline material by mechanical grinding to obtain a crystalline powder material with a size of 1-100 μm, and then ultrasonically dispersing the crystalline powder material in a DMF solution; 2) Weigh EC powder and add it to DMF, then heat and stir until completely dissolved, and transfer to room temperature to obtain EC solution; add the solution obtained in step 1) to the EC solution, and stir evenly at room temperature to obtain a mixed solution; 3) pouring the mixed solution of 2) into a square glass container, solidifying, cooling to room temperature, and then removing the film to obtain a Cd-MOF@EC composite membrane material; The molecular structure of the cadmium metal organic framework crystal material Cd-MOF is [Cd2(CBBD)(4,4ʹ-bpy)(EtOH)2] n , n=∞, the Cd-MOF unit structure is as follows: The mass ratio of the cadmium metal organic framework material crystal material Cd-MOF to EC powder is 0.1765:
1.
2. The method for preparing the Cd-MOF@EC composite membrane material according to claim 1, characterized in that: The preparation method of the cadmium metal organic framework crystal material Cd-MOF comprises the following steps: (1) H4CBBD, terminal bridge ligand 4,4'-bpy and Cd(NO3)2·4H2O are placed into a polytetrafluoroethylene liner, and then water and ethanol are added to form a mixed solvent, and the mixture is stirred and mixed to obtain a mixed solution; (2) The encapsulated polytetrafluoroethylene liner loaded in step (1) is loaded into a reactor and placed in an oven for hydrothermal reaction. After the reaction is completed, the temperature is lowered to the required temperature and then the oven is closed. The mixture is taken out after naturally cooling to room temperature and the crystal growth condition is observed under a microscope. The mixture is then filtered, allowed to stand, and allowed to dry naturally to obtain a cadmium metal organic framework material Cd-MOF.
3. The method for preparing the Cd-MOF@EC composite membrane material according to claim 2, characterized in that: In the step (1), the molar ratio of the ligand H4CBBD, the terminal bridging ligand 4,4'-bpy and Cd(NO3)2·4H2O is 1:2:2; based on 0.1 mmol Cd(NO3)2·4H2O, 4-7 mL of water and ethanol are required.
4. The method for preparing the Cd-MOF@EC composite membrane material according to claim 2, characterized in that: The temperature of the hydrothermal reaction in step (2) is 160°C, and the time of the hydrothermal reaction is 48-72 h. After the reaction is completed, the temperature is lowered to 80°C at a rate of 5°C / h, and then the temperature is stopped and the oven is closed. The oven is allowed to cool naturally to room temperature to obtain colorless crystals, namely, Cd-MOF crystal materials.
5. Application of the Cd-MOF@EC composite film material prepared by the preparation method according to any one of claims 1 to 4 in a TENG device, characterized in that: The Cd-MOF@EC composite film material is applied to the TENG device to realize self-driven lighting of white lamp beads, provide a visible light source, and promote the azidation reaction of the CH bond of the aldehyde compound.
6. The use according to claim 5, characterized in that: The Cd-MOF@EC composite film material is assembled into a TENG device, including the following steps: a. Cut the film into 5 × 5 cm 2 , glued to the sticky side of the Cu tape and bonded copper wire on the back with conductive silver glue as an external conductor; b. Spin-coat the PVDF film onto a copper sheet and cut into 5 × 5 cm 2 , and paste copper wire on the back of the copper sheet as another external conductor; c. Assemble the devices prepared in a and b above into a Cd-MOF@EC-TENG device based on Cd-MOF@PVDF composite membrane material; d. Connect the Cd-MOF@EC-TENG device and continuously power the white lamp bead group to provide a white light source to achieve visible light-induced azidation reaction of the CH bonds of aldehyde compounds.
Citation Information
Patent Citations
Cadmium metal organic framework material as well as preparation method and application thereof
CN115572391A